UNDERGRADUATE NURSING STUDENTS’ EXPERIENCES ENGAGING IN SERIOUS ILLNESS COMMUNICATION AND PERCEPTIONS OF SERIOUS ILLNESS CONVERSATION GUIDE TRAINING: A QUALITATIVE DESCRIPTIVE STUDY - Morkunas, Rachel (My University, 2020)
Background: While serious illness communication is an important aspect of nursing care, it is recognized as an area of practice for which nursing students are not adequately prepared. Communication tools such as the Serious Illness Conversation Guide (SICG) may help address these gaps in knowledge and skill. Aim: The aim of this study is to explore undergraduate nursing students’ experiences engaging in serious illness communication and their perceptions about participation in a SICG workshop that aimed to improve such communication. Methods: A qualitative descriptive approach was used. One-on-one, semi-structured interviews were conducted with eight undergraduate nursing students at McMaster University who had attended SICG training. Critical incident technique was used to elicit participant accounts of engaging in serious illness communication at their professional practice placements. Data were analyzed using qualitative techniques. Participants were surveyed to assess perceptions of the SICG workshop. Findings: Three themes related to undergraduate nursing students’ experiences engaging in serious illness communication after receiving SICG training were: a) serious illness communication is challenging to enact, b) finding moral and ethical ground, and c) fitting into the culture of the professional practice setting. Three themes related to nursing students’ perceptions of the SICG workshop were: a) applicability of SICG training to practice, b) strengths of SICG training, and c) limited opportunities to develop competence. Conclusions: Nursing students are challenged by serious illness communication in their practice. Findings support the integration of educational resources aimed to better prepare them for critical communication knowledge and skills on entry-to-practice.
UNDERGRADUATE NURSING STUDENTS’ EXPERIENCES ENGAGING IN SERIOUS ILLNESS COMMUNICATION
Keywords: serious illness communication; undergraduate nursing students